AUDIT TATA KELOLA TEKNOLOGI INFORMASI PADA LAYANAN AKADEMIK FAKULTAS SAINS DAN TEKNOLOGI MENGGUNAKAN COBIT 2019 - Suryani, Suryani; Dwinnie, Zairy Cindy; Dwynne, Zaira Cindya; Pramana, Jeki Harya; Megawati, Megawati (Universitas Komputer Indonesia, 2023)
The development of information technology requires universities to update and improve information technology infrastructure to face competition and take advantage of the times. Service is the main aspect that can facilitate public affairs in the higher education environment. The use of the COBIT 2019 Framework is considered an effective guide for implementing Information Technology in managing the Academic Information System at the Faculty of Science and Technology, Sultan Syarif Kasim Riau State Islamic University. This framework makes a valuable contribution to supporting overall Information Technology management. This research has a specific objective, which is to apply the COBIT 2019 Framework to design effective information technology governance in business and technology management. Hopefully, this research will provide relevant information related to the implementation of such governance. Keywords – Audit, COBIT 2019, Academic Information System